The intentionally unseen: exploring the illicit drug use of non-treatment seeking drug users in Scotland - McPhee, Iain (2012)
There is a perception that drug use is a serious and growing problem to be solved by medicine, social work and drug enforcement agencies. This thesis takes a critical standpoint again such populist views and interprets drug use as one of any number of normal activities that people engage. This qualitative research utilising a bricoleur ethnographic methodology focuses on the drug taking of non-treatment seeking illegal drug users. The data reveals that they manage several social identities and the potential stigma of being discovered as an illicit user of illegal drugs utilising several strategies to remain intentionally unseen. The thesis explores how and in what way socially competent drug users differ from visible treatment seeking drug users. In order to develop this understanding, several gatekeepers were identified and within their social networks the participants were recruited into this research. The participants (n=24) were recruited from a wide range of age groups (21-52) and geographical locations within Scotland. One to one interviews, a focus group, and several pair bonded partners were interviewed together providing rich sources of data. Interviews were transcribed and analysed thematically from a social constructionist perspective. The findings illuminate the ways in which the intentionally unseen identify and manage risks from drugs, drugs policy and the potential shame and stigma were their hidden social worlds revealed. The practical implications of the results of this thesis are explored and recommendations for future research are discussed